Urinary n-acetyl-beta-d-glucosaminidase Excretion: an Indicator of Neuropathy in Type 2 Diabetes - Kopf, S.; Oikonomou, D.; Zdunek, D.; von Eynatten, M.; Hess, G.; Nawroth, P. P.; Bierhaus, A.; Humpert, P. M. (Experimental and Clinical Endocrinology & Diabetes, 2013)
The established marker for tubular damage, urinary n-acetyl-beta-d-glucosaminidase is significantly increased in type 1 and 2 diabetes patients and is related to albuminuria and other diabetic complications. In this cross sectional study of type 2 diabetes patients with a history of albuminuria, we studied the relationship between excretion of n-acetyl-beta-d-glucosaminidase in urine and diabetic neuropathy.160 type 2 diabetes patients were screened for diabetic peripheral neuropathy and cardiovascular autonomic neuropathy. N-acetyl-beta-d-glucosaminidase excretion was detected in 24 h urine samples.Urinary excretion of n-acetyl-beta-d-glucosaminidase correlated significantly with glucose control (fasting glucose r=0.18; p=0.04; HbA1c r=0.20; p=0.02) and urine albumin excretion (r=0.22; p=0.01). Binary regression analyses showed that increased urinary n-acetyl-beta-d-glucosaminidase concentration is an independent predictor for presence of clinical symptoms of peripheral neuropathy (OR 1.8 [95%CI 1.2–2.74] and vibration deficiency [OR 1.7; 95% CI 1.2–2.66]. There was also a significant negative association between urinary n-acetyl-beta-d-glucosaminidase and E/I-Ratio (r=−0.21, p<0.02) as well as the 30:15-Ratio (r=−0.24; p<0.01) of heart rate variability. Furthermore, increased n-acetyl-beta-d-glucosaminidase excretion independently predicted cardiovascular autonomic diabetic neuropathy with an OR for decreased E/I-Ratio of 1.7 [95%CI 1.1–2.75]; (p<0.02) and 30:15-Ratio:OR 2.4 [95% CI 1.26–4.45]; (p<0.01).Urinary n-acetyl-beta-d-glucosaminidase excretion is an independent marker for diabetic peripheral and cardiovascular autonomic neuropathy in type 2 diabetic patients.
Keywords: type 2 diabetes; peripheral diabetic neuropathy; autonomic diabetic neuropathy; tubular damage; urinary NAG